Establishment of fundamental institutional framework through innovation law and policy relating to the rights of persons with disabilities in Malaysia (FRGS15-184-0425) - Mokhtar, Khairil Azmin (2019)
Persons with Disabilities (PWD) have been largely being discriminated against and denied of their rights. They face difficulties in having access to education, employment, accessibility and consequently jeopardized their right to live and participate in the society. The Convention on the Rights of Persons with Disabilities (CRPD) together with its Optional Protocol have been established in order to improve their livelihood so that the community could enjoy full and equal fundamental freedoms together with respect for their inherent dignity. The CRPD has changed the model of disability from medical/charity model to human rights-based model. The change of approach has positioned disability as an important dimension of human culture. It also ensures the PWD community is treated with dignity and equality. The CRPD has been ratified by most UN Members States including Malaysia. The country has signed and ratified the Convention in 2008 and 2010 respectively. In order to fulfil the international commitment, Malaysia has enacted the Persons with Disabilities Act 2008. Despite the ratification of CRPD and the enactment and amendment of relevant domestic laws to fulfil its obligations under the convention, Malaysia still hasn't fulfilled its responsibility properly. The monitoring mechanism for instance, as required to be created in each country under CRPD, has not been established by the government. Among the findings of this research are to propose amendments to domestic laws and policies and the establishment of systematic institutional implementation and independent monitoring mechanism. Experience from countries such as the United Kingdom, Australia and Ireland, which been regarded as role models in this area, would provide valuable guides and lessons to Malaysia. This research deals with doctrinal and jurisprudential discussions followed by analytical studies of laws, policies and institutional framework through primary and secondary legal and non-legal documents. It is qualitative research incorporating the study of applied law and the socio-legal dimension of the issues. Semi-structured interview and participant observation has been conducted. The outcome of this research includes various suggestions and recommendations on the improvement of legal, policies and institutional frameworks that can promote and protect the rights of PWD in Malaysia.